The Assessment Instruments of Social and Environment Literacy in Science Learning for Elementary School - Winarni, Endang Widi; Abdul Muktadir, ‎; Yusnia, Yusnia; Liani, Gita Agusti; Heryanto, Debi; Wulandari, Dwi (KnE Social Sciences, 2025)
This study aims to describe the characteristics of social and environmental literacy assessment instruments, the logical feasibility of assessment instruments, the empirical feasibility of assessment instruments, and the environmental literacy profile in science learning on natural appearance for elementary school. This research uses the ADDIE model and the R&D method. The research object is 18 students from the fifth-grade Elementary School 44 Bengkulu City in the 2023/2024 academic year. The instruments used were interview guidelines, questionnaires, and environmental literacy attitude questionnaires. Data analysis techniques include analysis of expert validation and reliability results, trial results, and environmental literacy profiles. The results show the following: The assessment instrument of social and environmental literacy consists of descriptors, tolerance, living in harmony and peace, and communication, while the natural environment consists of indicators of responsibility, awareness and concern, knowledge and understanding of problems, and repeated actions for maintenance. The environmental literacy assessment instrument has met the validity and reliability requirements of two validators. The social environmental literacy assessment instrument consists of 10 items, eight valid items were obtained, while for natural environmental literacy, all ten items were valid. Lastly, the percentage of environmental literacy in natural science learning on natural appearance material for fifth-grade elementary school students shows social literacy of 79.44% and environmental literacy of 87.3%.